CHINESE ANCIENT FOLK TRADITIONAL AUSPICIOUS PATTERNS IN MODERN CLOTHING DESIGN: AN EXAMPLE OF SU EMBROIDERY - DING , YI; KOLOSNICHENKO, O. (Art and Design, 2024)
Purpose. The paper explores how traditional Chinese auspicious patterns can be innovatively integrated into modern clothing design. It addresses maintaining cultural significance while adapting patterns to contemporary aesthetics, making them appealing to modern tastes through simplification, stylization, and updated color palettes. Methodology. The historical and cultural analysis method, literature analysis method, and case study method are used to analyze the evolution process, cultural connotation, and design application of traditional Chinese auspicious patterns. Results. The paper demonstrates that the integration of traditional Chinese auspicious patterns into modern clothing design can be achieved through innovative methods such as simplification and stylization. These approaches maintain the cultural essence of the patterns while making them relevant and appealing for contemporary fashion, thereby enhancing their practical value in modern design contexts. Scientific novelty. The paper introduces innovative methods for adapting traditional Chinese auspicious patterns to modern aesthetics through simplification and modernization, preserving their cultural essence while making them relevant for contemporary fashion. Practical significance. The study provides practical techniques for integrating these traditional patterns into modern clothing design, enhancing their appeal and usability in today's fashion industry.